Total Flavonoid Levels in n-hexane and Ethyl Acetate Fractions of Rosmarinus officinalis L. Leaves and Their Antibacterial and Antioxidant Activities - Esati, Ni Ketut; La, Elisabeth Oriana Jawa; Sudiasih, Ni Putu; Saniasih, Ni Nyoman Dina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The rosemary (Rosmarinus officinalis L.) is a plant of the Lamiaceae tribe that has not been widely studied regarding its pharmacological activity, known from previous studies to contain secondary metabolites of flavonoids. Flavonoids are phenol compounds with many pharmacological activities, including antibacterials and antioxidants. This study aims to determine the total flavonoid levels in R. officinalis leaves and their effect on antibacterial and antioxidant activities. This research began with the preparation of ethanol extract from R. officinalis leaves, then the fractionation of the extract produced n-hexane and ethyl acetate fractions. Total flavonoid levels were determined against both fractions by UV-Vis spectrophotometry. A test of the fraction’s antibacterial activity against Staphylococcus aureus was performed using the disc diffusion method. The antioxidant test is carried out by the DPPH method. The total flavonoid content of the ethyl acetate fraction is 47.437 ± 1.947%, higher than the n-hexane fraction. Test antibacterial and antioxidant activity showed more significant results in the ethyl acetate fraction than in the n-hexane fraction. In conclusion, the total flavonoid levels of ethyl acetate fraction are directly proportional to the antibacterial and antioxidant activities of R. officinalis leaves.